Correlation between serum ferritin, serum iron and blood glucose level in patients of type 2 diabetes mellitus (Journal of Dhaka National Medical College & Hospital, 2019)
Background: Diabetes Mellitus (DM) is a group of metabolic diseases characterized by hyperglycemia resulting from defects in insulin secretion, insulin action, or both. Ferritin is a ubiquitous intracellular protein complex that reflects the iron stores of the body. Many cross-sectional studies indicate that increased body iron stores have been associated with the development of glucose intolerance, type 2 diabetes,metabolic syndrome. This study was carried out to find out the relationship between serum ferritin, serum iron and type 2 diabetes and to see the influence of body iron storesand blood glucose.Methods: This study includes 81 patients suffering from type 2 diabetes and compared with controls at BIRDEM General Hospital. Serumferritin serum iron andFasting Blood Sugar (FBS) were measured.Results: Serum ferritin was significantly higher (p